The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: Description of four new species - Ghirotto, Victor Morais [UNESP]; Leite Guadanucci, José Paulo [UNESP]; Indicatti, Rafael Prezzi [UNESP] (Museum National d'Histoire Naturelle, Paris, France, 2021)
Four new species of the mygalomorph spider genus StenoterommataHolmberg, 1881 are described from Southeastern and Central Brazil. They are among the first described species that occur in the Brazilian Cerrado: S. neodiplornata Ghirotto & Indicatti, n. sp. from São Paulo state, in areas of Atlantic Forest, of savanna and of seasonal forest (Cerradão); S. chavarii Ghirotto & Indicatti, n. sp. from Botucatu, São Paulo state, in ecotonal areas of Atlantic Forest and Cerrado, as well as open anthropized areas similar to savannas; S. bodoquena Ghirotto & Indicatti, n. sp. from Bonito, Mato Grosso do Sul state, in areas of Atlantic Forest with Cerrado influences and seasonal forest; S. egric Ghirotto & Indicatti, n. sp. from Ibitipoca mountain range, Lima Duarte, Minas Gerais state, in Atlantic Forest and savanna areas. All new species are differentiated by the unique morphology of genitalia. Information on the natural history of S. neodiplornata Ghirotto & Indicatti, n. sp., S. bodoquena Ghirotto & Indicatti, n. sp. and S. egric Ghirotto & Indicatti, n. sp. is provided. Stenoterommata neodiplornata Ghirotto & Indicatti, n. sp. is the third species of the genus that can inhabit trunks and upper branches of the highest part of the trees. In addition, it is presented the first record of the genus for the Central Brazil, S. bodoquena Ghirotto & Indicatti, n. sp. from Mato Grosso do Sul.
Keywords: biodiversity; mygalomorph spiders; Mygalomorphae; Neotropics; new record; new species; Pycnothelinae; savanna; South America